(untitled) (Journal of the College of Basic Education, 2023)
This study was carried out on 60 ants samples collected from different places included: Gardens House, Food, died Cockroaches and W.C. Two methods were used: Isolation of bacteria from external surface and internal component, that to show the importance of this insect and their role in transferring of pathogenic bacteria. The results showed isolation of 30 isolates of different bacterial genus at 50%, included Staphylococcus aureus at highest ratio 26.23% then Escherichia coli, Bacillus subtilis, Klebsiella spp., Proteus spp., Pseudomonas areuginosa and Sarcinia at (23.34, 13.34, 13.34, 10, 6.67, 6.67)% respectively. The study revealed that the ants ply an important role in transferring these microbes. The majority of that isolates were on their external surface 63.33% in comparison to that isolated from internal component. The antibiotic sensitivity test for isolates against (7) antibiotics were resistance to multi antibiotics specially Vancomycin, whilst most isolates were sensitive to Nitrofurantin